Preparation and investigation of structure, magnetic and dielectric properties of (BaFe11.9Al0.1O19)1-x - (BaTiO3)x bicomponent ceramics. Issue 17 (1st December 2018) - Trukhanov, S.V.; Trukhanov, A.V.; Salem, M.M.; Trukhanova, E.L.; Panina, L.V.; Kostishyn, V.G.; Darwish, M.A.; Trukhanov, An.V.; Zubar, T.I.; Tishkevich, D.I.; Sivakov, V.; Vinnik, D.A.; et al.
Abstract: (BaFe11.9 Al0.1 O19 )1- x - (BaTiO3 ) x with x = 0, 0.25, 0.5, 0.75 and 1 bicomponent ceramics has been prepared from single-phase compounds of BaFe11.9 Al0.1 O19 ( x = 0) (BFO) and BaTiO3 ( x = 1) (BTO) by a standard ceramic technique. The constituent materials have been chosen considering their perspective ferrimagnetic and ferroelectric properties, respectively for BFO and BTO. Moreover, Ba-hexaferrites are reported to exhibit ferroelectricity at room temperature as well, and the combination of two ferroelectric phases is of interest. Systematic investigations of the structural, magnetic and dielectrical properties versus chemical composition ( x ) have been performed. The ferrimagnetic phase transition temperature is almost independent of the BTO content, which is determined by intensity of the Fe 3+ -O 2- -Fe 3+ indirect superexchange interactions in the BFO hexaferrite phase. However, the coercivity of composite samples is lower due to the contribution of the microstructure-dependent shape anisotropy to the total magnetic anisotropy energy. The permittivity vs. temperature behavior confirmed the existence of two ferroelectric phase transitions corresponding to structural phase transitions in BTO at 400 K and BFO at 700 K. It has been observed that the dielectrical properties of composite samples, including the temperatures of the phase transitions, critically depended on concentration x which affects the composite microstructure. This behavior has been discussed in terms of microstructure analysis and such parameters as the grain size, porosity and density.